Sulfide-based solid electrolytes and all-solid-state lithium-ion batteries
Patent Information
- Application Number
- JP2021162164
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-30
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-09-30
AI Technical Summary
【0011】 本発明によれば、良好なイオン伝導度を有する硫化物系固体電解質、及び、それを用いた全固体リチウムイオン電池を提供することができる。
Smart Images

Figure 0007648494000002 
Figure 0007648494000003 
Figure 0007648494000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a sulfide-based solid electrolyte and an all-solid-state lithium-ion battery. [Background technology]
[0002] In recent years, with the rapid spread of information-related devices and communication devices such as personal computers, video cameras, and mobile phones, the development of batteries to be used as power sources for these devices has become important. Among these batteries, lithium ion batteries have attracted attention from the viewpoint of their high energy density. In addition, high energy density and improved battery characteristics are also required for lithium secondary batteries for large-scale applications such as vehicle-mounted power sources and load leveling.
[0003] However, in the case of lithium-ion batteries, the electrolyte is mostly organic compounds, and even if a flame-retardant compound is used, the risk of fire cannot be completely eliminated. As an alternative to liquid-based lithium-ion batteries, solid-state lithium-ion batteries, which use a solid electrolyte, have been attracting attention in recent years. Among them, solid-state lithium-ion batteries that use sulfides such as Li2S-P2S5 as solid electrolytes or lithium halides added to them are becoming mainstream.
[0004] In addition, in order to improve the characteristics of all-solid-state lithium-ion batteries, solid electrolytes with high ion conductivity are required. In general, it is expected that lithium ion conductivity can be improved by increasing the lithium ion, which is a charge carrier. As such a technique, for example, Non-Patent Document 1 discloses a technique of replacing pentavalent P in an argyrodite-type Li7PS6 with tetravalent Si. [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] J. Mater. Chem. A, 7(2019)2717 Summary of the Invention
Problems to be Solved by the Invention
[0006] As the amount of substitution of pentavalent P in the sulfide-based solid electrolyte with a tetravalent element increases, the ionic conductivity improves accordingly. In this regard, in the technique described in Non-Patent Document 1 mentioned above, pentavalent P in argyrodite-type Li7PS6 is substituted with tetravalent Si, but only 40% of P is substituted and it cannot be completely substituted. Therefore, there is still room for improvement in the ionic conductivity of the sulfide-based solid electrolyte.
[0007] The present invention has been made to solve the above problems, and an object thereof is to provide a sulfide-based solid electrolyte having good ionic conductivity and an all-solid-state lithium-ion battery using the same.
Means for Solving the Problems
[0008] In an embodiment, the present invention completed based on the above findings is a sulfide-based solid electrolyte having an argyrodite-type structure, which is Li 8-x SiS 6-x-y Br x Te y (wherein, (1) 0 < x ≤ 1.25 and 0.25 ≤ y < 1.00, (2) 0 < x ≤ 1.00 and 1.00 ≤ y < 1.50, or (3) 0 < x ≤ 0.75 and y = 1.50). It is a sulfide-based solid electrolyte represented by
[0009] In another embodiment of the sulfide-based solid electrolyte of the present invention, in the above formula, (1') 0.25 ≤ x ≤ 0.75 and 0.50 ≤ y < 1.00, or (2') 0.25 ≤ x ≤ 0.75 and y = 1.00.
[0010] In still another embodiment, the present invention is an all-solid-state lithium-ion battery including a solid electrolyte layer, a positive electrode layer, and a negative electrode layer, which are composed of the sulfide-based solid electrolyte according to the embodiment of the present invention.
Effects of the Invention
[0011] According to the present invention, it is possible to provide a sulfide-based solid electrolyte having good ionic conductivity, and an all-solid-state lithium ion battery using the same. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic diagram of an all-solid-state lithium-ion battery according to an embodiment of the present invention. [Diagram 2] 1 is an X-ray diffraction (XRD) graph for Examples 1 to 10. [Diagram 3] 1 is an X-ray diffraction (XRD) graph for Examples 11 to 17. [Figure 4] 1 is an X-ray diffraction (XRD) graph for Comparative Examples 1 to 3 and Reference Examples 1 to 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Next, the embodiments of the present invention will be described in detail with reference to the drawings. It should be understood that the present invention is not limited to the following embodiments, and that appropriate changes and improvements in the design may be made based on the ordinary knowledge of those skilled in the art without departing from the spirit of the present invention.
[0014] (Sulfide solid electrolyte) The sulfide-based solid electrolyte of this embodiment is a sulfide-based solid electrolyte having an Argyrodite structure. The sulfide-based solid electrolyte can be confirmed to have the Argyrodite structure by, for example, X-ray diffraction measurement using CuKα radiation. The Argyrodite structure has strong diffraction peaks at 2θ=24.6±1.0° and 28.7±1.0°. The diffraction peaks of the Argyrodite structure may also appear at, for example, 2θ=15.0±1.0°, 17.3±1.0°, 30.0±1.0°, 42.8±1.5°, or 45.5±1.5°. The sulfide-based solid electrolyte of this embodiment may have these peaks.
[0015] The sulfide-based solid electrolyte of this embodiment may contain an amorphous component in part as long as it has an X-ray diffraction pattern of an argyrodite-type structure, and may contain a structure or raw materials other than the argyrodite-type structure.
[0016] The sulfide-based solid electrolyte of this embodiment has a composition represented by the formula: Li 8-x SiS 6-x-y Br x Te y (wherein, (1) 0 < x ≤ 1.25 and 0.25 ≤ y < 1.00, (2) 0 < x ≤ 1.00 and 1.00 ≤ y < 1.50, or (3) 0 < x ≤ 0.75 and y = 1.50). By substituting sulfur (S) in the solid electrolyte with bromine (Br) and tellurium (Te) having a large ionic radius, the ionic conduction path expands and the ionic conductivity is improved. Also, since the valence changes from divalent sulfur (S) to monovalent bromine (Br) and tellurium (Te), Li becomes more mobile. Therefore, a sulfide-based solid electrolyte having good ionic conductivity can be obtained. Also, by containing tellurium (Te), an argyrodite phase is obtained, which also improves the ionic conductivity.
[0017] In the sulfide-based solid electrolyte of this embodiment, if x exceeds 1.25 or y exceeds 1.50 in the above composition formula, there is a possibility that the argyrodite-type structure cannot be formed. In the sulfide-based solid electrolyte of this embodiment, in the above composition formula, it is preferable that (1') 0.25 ≤ x ≤ 0.75 and 0.50 ≤ y < 1.00, or (2') 0.25 ≤ x ≤ 0.75 and y = 1.00. According to such a configuration, a sulfide-based solid electrolyte having better ionic conductivity can be obtained. When the ionic conductivity of the sulfide-based solid electrolyte is good in this way, the voltage drop (IR drop) during discharge becomes small, so the battery capacity of the all-solid-state lithium-ion battery using it becomes high. Also, this effect becomes remarkable especially when the all-solid-state lithium-ion battery is at a high rate.
[0018] The average particle size of the sulfide-based solid electrolyte according to the embodiment of the present invention is not particularly limited, but may be 0.01 to 100 μm, 0.1 to 100 μm, or 0.1 to 50 μm.
[0019] The ionic conductivity of the sulfide-based solid electrolyte according to the embodiment of the present invention is 10 -4 S / cm or more is preferable, and 10 -3 S / cm or more is more preferable. The ionic conductivity of the sulfide-based solid electrolyte can be measured, for example, as follows. That is, 0.2 g of the sulfide-based solid electrolyte powder is pressed at a pressure of 550 MPa to form a plate shape, and then a pellet with a diameter of 10 mm is prepared by attaching gold electrodes to both sides of the plate. Using the pellet, AC impedance measurement from 20 Hz to 100 MHz is performed at 30°C with an applied voltage of 100 mV using an E4990A manufactured by Toyo Corporation with open-short correction. The Cole-Cole plot is analyzed by the AC impedance measurement to determine the migration resistance of Li ions. Next, the ionic conductivity is calculated from the migration resistance of Li ions and the thickness and area of the pellet used for the measurement based on the following formula. Ionic conductivity = pellet thickness / [(Li ion migration resistance) × (pellet area)]
[0020] (Method of manufacturing sulfide-based solid electrolyte) Next, a method for producing a sulfide-based solid electrolyte according to an embodiment of the present invention will be described. First, raw materials are weighed out to obtain a predetermined composition in a glove box with an inert gas atmosphere such as argon gas or nitrogen gas. Examples of the raw materials used here include Li, Li2S, Li2Te, LiTe3, LiBr, SiBr4, Br2, Si, SiS, SiS2, Si2Te3, S, and Te.
[0021] Next, the mixture is mixed in a mortar or the like for 5 to 30 minutes to prepare a mixed powder. At this time, it is preferable to mix for such a time that the average particle size of the mixed powder becomes 5 to 40 μm.
[0022] Next, the mixed powder is pelletized, vacuum sealed in a quartz ampoule, and sintered together with the quartz ampoule at 500 to 900°C for 1 to 20 hours to obtain a composition of the formula: Li 8-x SiS 6-x-y Br x Te y It is possible to prepare a sulfide-based solid electrolyte according to an embodiment of the present invention, which is represented by the following formula:
[0023] (All-solid-state lithium-ion battery) A solid electrolyte layer is formed by the sulfide-based solid electrolyte according to the embodiment of the present invention, and an all-solid-state lithium ion battery including the solid electrolyte layer, a positive electrode layer, and a negative electrode layer can be produced. The positive electrode layer and the negative electrode layer constituting the all-solid-state lithium ion battery according to the embodiment of the present invention are not particularly limited and can be formed of known materials and can have a known configuration as shown in FIG.
[0024] The positive electrode layer of the lithium ion battery is a layer of a positive electrode mixture obtained by mixing a known positive electrode active material for lithium ion batteries with the sulfide-based solid electrolyte according to the embodiment of the present invention or another sulfide-based solid electrolyte.
[0025] The positive electrode mixture may further include a conductive assistant. As the conductive assistant, a carbon material, a metal material, or a mixture thereof may be used. The conductive assistant may include at least one element selected from the group consisting of, for example, carbon, nickel, copper, aluminum, indium, silver, cobalt, magnesium, lithium, chromium, gold, ruthenium, platinum, beryllium, iridium, molybdenum, niobium, osmium, rhodium, tungsten, and zinc. The conductive assistant is preferably a highly conductive carbon element, a metal element, a mixture, or a compound containing carbon, nickel, copper, silver, cobalt, magnesium, lithium, ruthenium, gold, platinum, niobium, osmium, or rhodium. As the carbon material, for example, carbon black such as Ketjen Black, acetylene black, denka black, thermal black, and channel black, graphite, carbon fiber, activated carbon, and the like may be used.
[0026] The average thickness of the positive electrode layer of the lithium ion battery is not particularly limited and can be appropriately designed depending on the purpose. The average thickness of the positive electrode layer of the lithium ion battery may be, for example, 1 μm to 100 μm, or 1 μm to 10 μm.
[0027] The method for forming the positive electrode layer of the lithium ion battery is not particularly limited and can be appropriately selected depending on the purpose. For example, the method for forming the positive electrode layer of the lithium ion battery includes sputtering using a target material of the positive electrode active material, or compression molding of the positive electrode active material.
[0028] The negative electrode layer of the lithium ion battery may be a layer of a known negative electrode active material for lithium ion batteries, or a layer of a negative electrode mixture obtained by mixing a known negative electrode active material for lithium ion batteries with the sulfide-based solid electrolyte according to the embodiment of the present invention or another sulfide-based solid electrolyte.
[0029] The negative electrode layer may contain a conductive assistant, as in the positive electrode layer. The conductive assistant may be the same material as that described in the positive electrode layer. As the negative electrode active material, for example, a carbon material, specifically, artificial graphite, graphite carbon fiber, resin-calcined carbon, pyrolytic vapor-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-calcined carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, non-graphitizable carbon, or a mixture thereof may be used. As the negative electrode material, for example, a metal itself, such as metallic lithium, metallic indium, metallic aluminum, or metallic silicon, or an alloy in combination with other elements or compounds may be used.
[0030] The average thickness of the negative electrode layer of the lithium ion battery is not particularly limited and can be appropriately selected depending on the purpose. The average thickness of the negative electrode layer of the lithium ion battery may be, for example, 1 μm to 100 μm, or 1 μm to 10 μm.
[0031] The method for forming the negative electrode layer of the lithium ion battery is not particularly limited and can be appropriately selected depending on the purpose. Examples of the method for forming the negative electrode layer of the lithium ion battery include sputtering using a target material of the negative electrode active material, compression molding of the negative electrode active material, and vapor deposition of the negative electrode active material.
[0032] The average thickness of the solid electrolyte layer of the lithium ion battery formed by the sulfide-based solid electrolyte according to the embodiment of the present invention is not particularly limited and can be appropriately designed according to the purpose. The average thickness of the solid electrolyte layer of the lithium ion battery may be, for example, 1 μm to 500 μm, or 50 μm to 100 μm.
[0033] The method for forming the solid electrolyte layer of the lithium ion battery is not particularly limited and can be appropriately selected depending on the purpose. For example, the method for forming the solid electrolyte layer of the lithium ion battery includes sputtering using a target material of the solid electrolyte, or compression molding of the solid electrolyte.
[0034] Other members constituting the lithium ion battery are not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include a positive electrode collector, a negative electrode collector, and a battery case.
[0035] The size and structure of the positive electrode current collector are not particularly limited and can be appropriately selected depending on the purpose. Examples of the material for the positive electrode current collector include die steel, stainless steel, aluminum, aluminum alloys, titanium alloys, copper, gold, and nickel. The positive electrode current collector may be in the form of, for example, a foil, a plate, or a mesh. The average thickness of the positive electrode current collector may be, for example, 10 μm to 500 μm, or 50 μm to 100 μm.
[0036] The size and structure of the negative electrode current collector are not particularly limited and can be appropriately selected depending on the purpose. Examples of the material for the negative electrode current collector include die steel, gold, indium, nickel, copper, and stainless steel. The negative electrode current collector may be in the form of, for example, a foil, a plate, or a mesh. The average thickness of the negative electrode current collector may be, for example, 10 μm to 500 μm, or 50 μm to 100 μm.
[0037] The battery case is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include known laminate films that can be used in conventional all-solid-state batteries, etc. Examples of the laminate film include a resin laminate film and a film in which a metal is vapor-deposited on a resin laminate film. The shape of the battery is not particularly limited and can be appropriately selected depending on the purpose. Examples of the shape of the battery include cylindrical, square, button, coin, and flat types. EXAMPLES
[0038] The following examples are provided to provide a better understanding of the present invention and its advantages, but the present invention is not limited to these examples.
[0039] Example 1 The raw materials were weighed in a glove box with an argon atmosphere so as to obtain a predetermined composition, and mixed in a mortar for 15 minutes to produce a mixed powder. The mixed powder was then pelletized into 1 g pellets and placed in a carbon crucible. The carbon crucible and the quartz ampoule were then vacuum sealed and fired at 700°C for 8 hours to obtain Li 7.75 SiS 5.50 Br 0.25 Te 0.25 A sulfide-based solid electrolyte having the following composition was obtained. The composition of the sulfide-based solid electrolyte was determined by weighing out 0.5 g of a sample (powder), dissolving it in various acids, and then analyzing it using an inductively coupled plasma optical emission spectrometer (ICP-OES) "PS7800" manufactured by Hitachi High-Tech Corporation. 0.2 g of this sulfide-based solid electrolyte powder was pressed under a pressure of 550 MPa to form a plate, and then a pellet with a diameter of 10 mm was prepared by attaching gold electrodes to both sides of the plate. Using the pellet, AC impedance measurement from 20 Hz to 100 MHz was performed at 30°C with an applied voltage of 100 mV using an E4990A manufactured by Toyo Corporation, which was subjected to open-short correction. From the AC impedance measurement, the Cole-Cole plot was analyzed to determine the Li-ion migration resistance. Next, the ionic conductivity was calculated from the Li-ion migration resistance and the thickness and area of the pellet used for the measurement based on the following formula. Ionic conductivity = pellet thickness / [(Li ion migration resistance) × (pellet area)]
[0040] In addition, X-ray diffraction (XRD: X-ray diffraction) graphs were obtained for the sulfide-based solid electrolyte samples by X-ray diffraction measurement using CuKα rays. Figures 2 to 4 show XRD graphs for Examples 1 to 17, Comparative Examples 1 to 3, and Reference Examples 1 to 4. In the XRD graphs, the Intensity in "Intensity (au)" represents the intensity of the X-rays detected in the XRD measurement, and au is an abbreviation for arbitrary unit and represents an arbitrary unit. In the XRD graphs, "2θ" represents the angle (diffraction angle) between the incident X-ray direction and the diffracted X-ray direction. Based on the XRD graphs, the presence or absence of a diffraction peak of an argyrodite structure was confirmed, thereby evaluating whether the sulfide-based solid electrolyte samples had an argyrodite structure.
[0041] Example 2 The composition of the sulfide-based solid electrolyte we prepared is Li 7.50 SiS 5.25 Br 0.50 Te 0.25 The same procedure as in Example 1 was carried out, except that the firing temperature was 600°C.
[0042] Example 3 The composition of the sulfide-based solid electrolyte we prepared is Li 7.25 SiS 5.00 Br0.75 Te 0.25 The procedure was carried out in the same manner as in Example 1, except that:
[0043] Example 4 The composition of the sulfide-based solid electrolyte we prepared is Li 7.00 SiS 4.75 Br 1.00 Te 0.25 The same procedure as in Example 1 was carried out, except that the firing temperature was 600°C.
[0044] Example 5 The composition of the sulfide-based solid electrolyte we prepared is Li 6.75 SiS 4.50 Br 1.25 Te 0.25 The procedure was carried out in the same manner as in Example 1, except that:
[0045] Example 6 The composition of the sulfide-based solid electrolyte we prepared is Li 7.75 SiS 5.25 Br 0.25 Te 0.50 The procedure was carried out in the same manner as in Example 1, except that:
[0046] Example 7 The composition of the sulfide-based solid electrolyte we prepared is Li 7.50 SiS 5.00 Br 0.50 Te 0.50 The procedure was carried out in the same manner as in Example 1, except that:
[0047] Example 8 The composition of the sulfide-based solid electrolyte we prepared is Li 7.25 SiS 4.75 Br 0.75 Te 0.50 The procedure was carried out in the same manner as in Example 1, except that:
[0048] Example 9 The composition of the sulfide-based solid electrolyte we prepared is Li 7.00 SiS 4.50 Br 1.00 Te 0.50The same procedure as in Example 1 was carried out, except that the firing temperature was 600°C.
[0049] Example 10 The composition of the sulfide-based solid electrolyte we prepared is Li 6.75 SiS 4.25 Br 1.25 Te 0.50 The same procedure as in Example 1 was carried out, except that the firing temperature was 500°C.
[0050] Example 11 The composition of the sulfide-based solid electrolyte we prepared is Li 7.75 SiS 4.75 Br 0.25 Te 1.00 The same procedure as in Example 1 was carried out, except that the firing temperature was 600°C.
[0051] Example 12 The composition of the sulfide-based solid electrolyte we prepared is Li 7.50 SiS 4.50 Br 0.50 Te 1.00 The same procedure as in Example 1 was carried out, except that the firing temperature was 600°C.
[0052] Example 13 The composition of the sulfide-based solid electrolyte we prepared is Li 7.25 SiS 4.25 Br 0.75 Te 1.00 The same procedure as in Example 1 was carried out, except that the firing temperature was 600°C.
[0053] Example 14 The composition of the sulfide-based solid electrolyte we prepared is Li 7.00 SiS 4.00 Br 1.00 Te 1.00 The same procedure as in Example 1 was carried out, except that the firing temperature was 600°C.
[0054] Example 15 The composition of the sulfide-based solid electrolyte we prepared is Li7.75 SiS 4.25 Br 0.25 Te 1.50 The same procedure as in Example 1 was carried out, except that the firing temperature was 600°C.
[0055] Example 16 The composition of the sulfide-based solid electrolyte we prepared is Li 7.50 SiS 4.00 Br 0.50 Te 1.50 The same procedure as in Example 1 was carried out, except that the firing temperature was 600°C.
[0056] (Example 17) The composition of the sulfide-based solid electrolyte we prepared is Li 7.25 SiS 3.75 Br 0.75 Te 1.50 The same procedure as in Example 1 was carried out, except that the firing temperature was 500°C.
[0057] Comparative Example 1 The composition of the sulfide-based solid electrolyte we prepared is Li 6.50 SiS 4.00 Br 1.50 Te 0.50 The same procedure as in Example 1 was carried out, except that the firing temperature was 500°C.
[0058] Comparative Example 2 The composition of the sulfide-based solid electrolyte we prepared is Li 6.75 SiS 3.75 Br 1.25 Te 1.00 The same procedure as in Example 1 was carried out, except that the firing temperature was 600°C.
[0059] Comparative Example 3 The composition of the sulfide-based solid electrolyte we prepared is Li 7.00 SiS 3.50 Br 1.00 Te 1.50 The same procedure as in Example 1 was carried out, except that the firing temperature was 500°C.
[0060] (Reference example 1) The composition of the sulfide-based solid electrolyte we prepared is Li 8.00 SiS 5.75 Te 0.25 The procedure was carried out in the same manner as in Example 1, except that:
[0061] (Reference example 2) The composition of the sulfide-based solid electrolyte we prepared is Li 8.00 SiS 5.50 Te 0.50 The same procedure as in Example 1 was carried out, except that the firing temperature was 800°C.
[0062] (Reference example 3) The composition of the sulfide-based solid electrolyte we prepared is Li 8.00 SiS 5.00 Te 1.00 The same procedure as in Example 1 was carried out, except that the firing temperature was 800°C.
[0063] (Reference example 4) The composition of the sulfide-based solid electrolyte we prepared is Li 8.00 SiS 4.50 Te 1.50 The same procedure as in Example 1 was carried out, except that the firing temperature was 600°C. The test results are shown in Table 1.
[0064] [Table 1]
[0065] (Evaluation Results) The solid electrolytes of Examples 1 to 17 all had strong diffraction peaks at 2θ=24.6±1.0° and 28.7±1.0° in the XRD graph, and had an argyrodite structure. The solid electrolytes of Comparative Examples 1 to 3 did not have such strong diffraction peaks at 2θ=24.6±1.0° and 28.7±1.0° in the XRD graph as those of Examples 1 to 17. The solid electrolytes of Examples 1 to 17 were each represented by the formula: Li 8-x SiS 6-x-y Brx Te y (In the formula, (1)0 <x≦1.25、且つ、0.25≦y<1.00、(2)0<x≦1.00、且つ、1.00≦y<1.50、または、(3)0<x≦0.75、且つ、y=1.50である。)で示す組成を有していたが、比較例1~3は当該組成を有していなかった。 Therefore, the solid electrolytes according to Examples 1 to 17 had better ion conductivity than those according to Comparative Examples 1 to 3, which did not have the above composition and did not have an argyrodite structure. Therefore, it is expected that the battery capacity of the all-solid-state lithium ion battery using the solid electrolytes according to Examples 1 to 17 will be improved.< / x≦1.25、且つ、0.25≦y<1.00、(2)0<x≦1.00、且つ、1.00≦y<1.50、または、(3)0<x≦0.75、且つ、y=1.50である。)で示す組成を有していたが、比較例1~3は当該組成を有していなかった。
Claims
1. A sulfide-based solid electrolyte having an argyrodite structure, Li 8-x SiS 6-x-y Br x Te y (In the formula, (1) 0<x≦1.25 and 0.25≦y<1.00, (2) 0<x≦1.00 and 1.00≦y<1.50, or (3) 0<x≦0.75 and y=1.50 It is.) A sulfide-based solid electrolyte represented by the formula:
2. In the above formula, (1') 0.25≦x≦0.75 and 0.50≦y<1.00, or (2') 0.25≦x≦0.75 and y=1.00, The sulfide-based solid electrolyte according to claim 1 .
3. 3. An all-solid-state lithium ion battery comprising a solid electrolyte layer made of the sulfide-based solid electrolyte according to claim 1, a positive electrode layer, and a negative electrode layer.